2016
DOI: 10.1038/cdd.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

p53 isoforms regulate astrocyte-mediated neuroprotection and neurodegeneration

Abstract: Bidirectional interactions between astrocytes and neurons have physiological roles in the central nervous system and an altered state or dysfunction of such interactions may be associated with neurodegenerative diseases, such as Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS). Astrocytes exert structural, metabolic and functional effects on neurons, which can be either neurotoxic or neuroprotective. Their neurotoxic effect is mediated via the senescence-associated secretory phenotype (SASP) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 64 publications
8
166
0
Order By: Relevance
“…Neurotoxic effects of astrocytes are mediated by SASP involving pro-inflammatory cytokine secretion (e.g., Il-6), while neuroprotection is mediated by neurotropic growth factors such as NGF [126]. Turnquist et al reported the expression of two isoforms of p53 in astrocytes, ∆133p53 and p53β; in in vitro primary human senescent astrocytes, a decreased expression of the isoform ∆133p53 was reported, and the decreased expression of this isoform, linked to neuroprotection, was attributed to autophagic degradation [127]. These findings suggest that regulatory mechanisms of p53 isoforms may represent a potential target for therapeutic strategies.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Neurotoxic effects of astrocytes are mediated by SASP involving pro-inflammatory cytokine secretion (e.g., Il-6), while neuroprotection is mediated by neurotropic growth factors such as NGF [126]. Turnquist et al reported the expression of two isoforms of p53 in astrocytes, ∆133p53 and p53β; in in vitro primary human senescent astrocytes, a decreased expression of the isoform ∆133p53 was reported, and the decreased expression of this isoform, linked to neuroprotection, was attributed to autophagic degradation [127]. These findings suggest that regulatory mechanisms of p53 isoforms may represent a potential target for therapeutic strategies.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…48 p53 and its isoforms are associated with development of neurodegenerative diseases such as Parkinson's and Alzheimer's because of its induction of cell death in response to stress and interaction with distinct cellular factors that have the ability to facilitate the development of these diseases. 49, 50, 51, 52 …”
Section: The Role Of P53 In Nerve Regenerationmentioning
confidence: 99%
“…We suggest that IL-6 in combination with the reduction in VEGF and BDNF plays a part in the impairment of 5xFAD astrocytes to support neurons. In line with this concept, Turnquist et al's study showed that while young astrocytes (early passage) displayed an increase in neuroprotective growth factors, which resulted in normal neurons, there was an increase in IL-6 secretion in senescent astrocytes (late passage) followed by apoptosis of neurons (42). Those authors also reported that brain sections from deceased patients with AD had increased numbers of senescent astrocytes as well as an increase in IL-6 expression (42).…”
Section: Discussionmentioning
confidence: 91%